Consumer perception of cultivated meat - Borusiak, B.; Bogueva, Diana; Marinova, Dora (Springer, 2024)
This book is a timely overview of the various aspects of consumer perception related to food. This book explores consumer perceptions that are vital to marketers and often underlie the success or failure of products in the marketplace.